Physical and genetic map of Epinotia aporema granulovirus genome - Parola, Alejandro Daniel (2002)
The bean shoot borer, Epinotia aporema (Lep. Tortricidae), is an economically important pest of legume crops in South America. Recently, a granulovirus (EpapGV) was isolated from E. aporema larvae, and evaluated as a potential biological control agent. In order to generate a restriction map and to investigate the gene organisation of EpapGV genome, DNA isolated from occlusion bodies as well as a set of cloned genomic fragments were analysed using combinations of restriction endonucleases and Southern blot analyses that lead to a first version of the physical map. It was subsequently confirmed and refined by sequencing the termini of the cloned fragments and assessing their contiguity by comparing the sequences with databases to identify putative ORFs spanning neighbour fragments. This was also aided by PCR amplifications with primers that pointed outwards of the cloned viral DNA. The granulin gene was positioned on the physical map, cloned and sequenced. Its 747-nucleotide-long ORF encodes a predicted protein of 29 kDa and the core of the baculovirus very late promoter ATAAG was found 29 nucleotides upstream the initiation codon. In addition, 27 putative ORFs were located on the map and used to explore the genome organisation by GeneParityPlot against the fully sequenced granulovirus genomes. These data, taken together with the phylogenetic tree generated by alignment of the major occlusion proteins, indicate that EpapGV is closely related to CpGV, but has a distinct gene organisation.